Kualitas Pelayanan Penerimaan Beras Sejahtera (Rastra) Di Desa Binangga Kecamatan Parigi Tengah Kabupaten Parigi Moutong - Tri Wahyuni; Slamet Riadi; Suasa Suasa; Haedar Akib; Hasan Rachmany (Jurnal Pajak dan Bisnis, 2020)
This study aims to determine the quality of receiving services for Prosperous Rice in Binangga Village, Central Parigi District. The basis of the research used is qualitative and type of research that is descriptive. Where the withdrawal for informants is done by Purpossive techniques. Data types are primary and secondary data. Data collection techniques used are library research, field research (observation, interviews, and documentation). While the informants numbered 9 people. The aspects used in the study consisted of 5 indicators proposed by Zeithami, Parasuraman, Berry, (Harbani Pasolong) which were used to measure service quality. where the five indicators are Tangibles (Physical Appearance), Reability (Reliability), Responsiveness (Reaponsive) (Assurance), Assurance (Guarantee), Emphaty (Treatment or Attention). Based on the results of the research obtained, it can be concluded that the Prosperous Rice Service Quality in Central Parigi District, Parigi Moutong District has not run well seen from the five indicators used in terms of Tangibles, Reability, Responsiveness, Assurance, Emphaty (Treatment or Attention). In terms of physical appearance in terms of facilities and infrastructure in the village it is not yet adequate, in terms of responsiveness in providing services that have not been appropriate and fast in serving the community, and in terms of empathy or attitude of justice provided by the officers who are responsible for distributing prosperous rice have not fully applied fair in providing services to the community.